ANALYSIS OF BUSINESS PROFIT LEVEL AND PROCESSING PRODUCTION ELASTICITY AT CV. AMFOANG JAYA IN SIKUMANA VILLAGE, MAULAFA DISTRICT, KUPANG CITY - Yosefiano Triantoro Hamu; Fredrik L. Benu; Aplonia Bani (Buletin Ilmiah Impas, 2026)
This study aims to analyze the factors influencing production, business profitability, and production elasticity in a honey processing business at CV. Amfoang Jaya, Sikumana Village, Maulafa District, Kupang City. The research method used was a case study with a quantitative approach. Data were collected through interviews, observations, questionnaires, and documentation, then analyzed using business profit analysis and the Cobb-Douglas production function in natural logarithm form.The results showed that capital, labor, raw materials, and demand simultaneously significantly influenced honey production, with a significance value of 0.003 (<0.05) and a coefficient of determination (R²) of 0.877. Partially, raw materials and demand had a positive and significant effect on production, while capital and labor did not. The average total business revenue was Rp30,430,000 per month, with total costs of Rp16,800,361 per month, resulting in an average profit of Rp13,629,639 per month. The business profit level reached 81.13%, which is considered high. Maximum profit analysis indicates that optimal production is achieved at an output level of 185,000 ml per month. The results of the production elasticity analysis indicate that all input variables are inelastic, with a total elasticity of 0.688, indicating decreasing returns to scale. Therefore, CV. Amfoang Jaya's honey processing business is considered profitable, but increasing production is more effective through efficient use of production factors, particularly raw materials.